Games Approach Implementation: Improvement of Basic Swimming Exercises in Introduction to Water for Preschool, Kindergarten, and School Age Categories - Diky Hadyansah; Rahmat Hidayatuloh; Sony Hasmarita; Rafdal Saeful Bakhri (JUARA : Jurnal Olahraga, 2022)
This study aims to determine the increase in basic swimming training by introducing water techniques in the preschool, kindergarten and school-age categories. This study involved 102 swimming school students in testing the validity and reliability, and 97 students were used as research samples using accidental sampling. The research was conducted at the Bandung International Swimming School Swimming Club. The instrument used in this research is the Swimming Games Program questionnaire given to Bandung International Swimming School trainers. The data obtained were then tested statistically using SPSS Version 24 with a significance level of α = 0.05 using the paired sample t-test. The implications of this research can provide information to swimming coaches and parents that swimming games programs have the potential to help train children in increasing courage and basic swimming techniques.